Prescriptive and Descriptive Alliteration in the Development of the Arabic Language, Comparative Study of Learning Theories and Grammar - Sulaikho, Siti; Nurhadi, Nurhadi; Wargadinata, Wildana; Amalia, Dian Risky (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
يحاول هذا البحث تحليل الخصائص الوصفية والتوجيهية لقواعد اللغة العربية. وبعد ذلك، يحاول هذا البحث اكتشاف نقاط الضعف في القواعد النحوية الوصفية والنحوية والتوجيهية. ومصادر البيانات المقالات التي تتعلق بالوصفية والتوجيهية في اللغة العربية. وأما الطريقة المستخدمة في هذا البحث فهي أبحاث المكتبات، وأما تقنيات تحليل البيانات فتستخدم تحليل المحتوى. أظهرت نتائج البحث أن المصطلحين التوجيهي والوصفي يستخدمان كتمييز بين النحو القياسي والقواعد البديلة. يتم تعريف القواعد القياسية على أنها صيغ ثابتة ومحددة ومنهجية في القواعد. ويتم تعريف القواعد البديلة على أنها بنية مرنة للغة لتسهيل استخدام اللغة وفهمها، مع مراعاة عناصر تطوير اللغة. كما توصلت نتائج البحث إلى وجود ثماني فرق بين النظرية الوصفية والتوجيهية كنظرية تعلم ، وأربع عشرة خاصية من خصائص الوصفية والتوجيهية كقواعد اللغة العربية، بالإضافة إلى ستة أمور في ضعف النحو التوجيهي والنحو الوصفي. كان استخدام المصطلحات الوصفية والتوجيهية في اللغة العربية جديدا نسبيا لأن استخدام هذين المصطلحين بشكل أكبر كنظريات في التعليم. يسعى هذا البحث إلى تحديد الاختلافات بين الوصفية والتوجيهية كنظرية التعلم. علاوة على ذلك. The use of prescriptive and descriptive terms in Arabic is relatively new because these two terms have been used more as theories in education. This research seeks to identify the differences between prescriptive and descriptive as a learning theory. Furthermore, this research attempts to analyze the prescriptive and descriptive characteristics of Arabic grammar. Then, this research tries to detect weaknesses in prescriptive grammar and descriptive grammar. The method used in this research is library research, meanwhile data analysis techniques use content analysis. The primary data source is in the form of journal articles that examine prescriptive and descriptive matters. Secondary sources are website articles that support research.The research results show that the terms prescriptive and descriptive are used as a distinction between standard grammar and alternative grammar. Standard grammar is defined as formulas in grammar that are fixed, definite and systematic. Alternative grammar is defined as a flexible structure of language to facilitate the use and understanding of language, taking into account elements of language development. The research results also found 8 points difference between prescriptive and descriptive as a learning theory, 14 characteristics of prescriptive and descriptive as Arabic grammar, as well as 6 weaknesses in prescriptive grammar and descriptive grammar.